Biometrics of neonates and characterization of the Amazon Turtle (Podocmenis expansa) nests in the Crixás-açu river, Mundo Novo, Goiás, Brazil - Navarro, Rodrigo Diana; Souza, Amanda Azevedo Rodrigues de; Navarro, Fernanda Keley Silva Pereira (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2023)
The objective of this study was to evaluate newborn biometrics and characterization of Podocnemis expansa turtle nests in the Crixás-Açu rivers, municipalities of Mundo Novo, Goais, Brazil. It consists of evaluating the newborns and the characterization of the nests after hatching. There was no statistical difference between eggs with oil, predatory nests, dead newborns, un hatched eggs, shell (total number of eggs counted within a nest), as well as hatching and survival rates for the distance of 30 meters from the river course. Animal weight, hoof length, hoof width, plastron length, plastron width or number of shields were obtained statistically significant considering the same fixed distance of 30 or greater than 30 meters from the river bank. In the eggshell analysis, there was a statistical difference regarding the amount of the element "Carbon" found, unlike the samples of pH, "phosphorus", "potassium", "hydrogen", "aluminium", "calcium", "magnesium" and matter. Organic. As for the particle size analysis of the sand extracted from the nests, there was a statistical difference in two sizes; 1 and 2 millimeters. This study shows that nests near vegetation are more successful in hatching.